2017
DOI: 10.3917/crii.076.0041
|View full text |Cite
|
Sign up to set email alerts
|

« On ne fait pas de politique ! » Les pratiques de dépolitisation au PNUD et au PNUE

Abstract: Distribution électronique Cairn.info pour Presses de Sciences Po. © Presses de Sciences Po. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The focus on practices, encouraged by the practice turn in international relations (PTIR), has contributed to a better understanding of IOs’ day‐to‐day activities both at the headquarters and in the field (Græger, 2017; Müller, 2018; Niezen and Sapignoli, 2017). It helped reconstruct the production and diffusion of international documents and artefacts (Adler‐Nissen and Drieschova 2020; Dimitrov, 2016; Fresia, 2014; Maertens and Parizet, 2017; Siroux, 2008); following the strategies of marginalized actors to internationalize their voices (Suiseeya and Zanotti, 2019); and exploring IOs as sites of knowledge generation (Bueger, 2015). The PTIR has also contributed to open up the debate about change in the practices of IOs following constraints and opportunities that are both endogenous and exogenous, cultural and material (Bode, 2018; Hopf, 2018).…”
Section: The Practices and Procedures Of International Organizationsmentioning
confidence: 99%
“…The focus on practices, encouraged by the practice turn in international relations (PTIR), has contributed to a better understanding of IOs’ day‐to‐day activities both at the headquarters and in the field (Græger, 2017; Müller, 2018; Niezen and Sapignoli, 2017). It helped reconstruct the production and diffusion of international documents and artefacts (Adler‐Nissen and Drieschova 2020; Dimitrov, 2016; Fresia, 2014; Maertens and Parizet, 2017; Siroux, 2008); following the strategies of marginalized actors to internationalize their voices (Suiseeya and Zanotti, 2019); and exploring IOs as sites of knowledge generation (Bueger, 2015). The PTIR has also contributed to open up the debate about change in the practices of IOs following constraints and opportunities that are both endogenous and exogenous, cultural and material (Bode, 2018; Hopf, 2018).…”
Section: The Practices and Procedures Of International Organizationsmentioning
confidence: 99%
“…We may think, however, that, despite all problems and stalemates, the process has moved forward and can, and will surely, move further in the direction of seriously addressing the problems that beset us (Dahan, 2016 ). Yet it is important to bring out and stand against the ‘depoliticisation’ of the debate and, as this article has laid out, of the lexicon we have previously examined, which is indeed underpinned by political issues and choices, despite their apparent technicality (see for instance, for other, related issues, either encompassing or regarding the environment the following authors, though only the last cursorily deals with climate change: Petiteville, 2018 ; Maertens & Parizet, 2017 ; Louis & Maertens, 2021 ).…”
Section: Lexicon and Powermentioning
confidence: 96%
“…An emerging body of literature has started to focus on depoliticisation as an intentional process through which political problems are presented in technical terms in order to insulate policymaking, pre-empt conflicts and eventually push for certain reforms ( Maertens and Parizet 2017 ;Maertens 2018 ;Stone 2017 ). The depoliticisation can be defined as "the set of processes (including varied tactics, strategies, and tools) that remove or displace the potential for choice, collective agency, and deliberation around a particular political issue" ( Hay 2014 : 293).…”
Section: Depoliticisation Techniquesmentioning
confidence: 99%
“…Scholars have shown that depoliticisation takes place in both domestic and supranational arenas, through institutional mechanisms, such as the creation of delegated agencies to advise on and make policy decisions, new forms of indirect and/or privatised governance such as "global public-private partnerships" and private "self-regulation" initiatives ( Stone 2017 ;Beveridge and Naumann 2014 ), framing tactics designed to technicalise issues ( Maertens 2017 ) or what has been called "depoliticised political discourses" ( Bourdieu 1982 : 155). In anthropology, recent insights have portrayed international bureaucracies as "anti-politics machines", which produce consensus through a discourse of harmony as a way of not addressing political controversies ( Müller 2013 ).…”
Section: Depoliticisation Techniquesmentioning
confidence: 99%